OSL Chronology of the Siling Co Paleolithic Site in Central Tibetan Plateau - Luo, Lan; Lai, Zhongping; Zheng, Wenhao; Xu, Yantian; Yu, Lupeng; Huang, Chang; Tu, Hua (Frontiers in Earth Science, 2021)
When and how was the Tibetan Plateau (TP), one of the least habitable regions on Earth, occupied by humans are important questions in the research of human evolution. Among tens of Paleolithic archaeological sites discovered over the past decades, only 5 are considered coeval with or older than the Last Glacial Maximum (LGM, ~27–19 ka). As one of them, Siling Co site in central TP was announced to ~40–30 ka based on radiocarbon dating and stratigraphic correlation. Given loose chronological constrain in previous studies, here we re-examined the chronology of Siling Co site with the optically stimulated luminescence (OSL) dating technique. Four sections from the paleo-shoreline at an elevation of ~4,600 m in the southeastern Siling Co were investigated, with stone artifacts found from the ground surface. Dating results of 9 samples delineated the age of ~4,600-m paleo-shoreline to be ~10–7 ka (~8.54 ± 0.21 ka in average). This age indicates the Siling Co site is not earlier than the early Holocene, much younger than the former age. The revised age of Siling Co site is consistent with the wet and humid climate conditions on the TP during early Holocene.